2013
DOI: 10.4081/jlimnol.2013.e2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on oxygen uptake and nutrient flux in sediment inhabited by molluscs

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In lentic waters, turbidity could be hastened and concentrations in nutrients and organic material higher due to the resuspension of sediments to the water column through bioturbation by fish (e.g., Breukelaar et al, 1994;Matsuzaki et al, 2009), resulting subsequently in phytoplankton blooming and water eutrophication, already enhanced by warming (Jeppesen et al, 2010). Changes in community composition (Matsuzaki et al, 2009) and vertical distribution of benthic fauna (Persson and Svensson, 2006b) due to predation by benthivorous fish may also impact nutrients fluxes as well as the incorporation of organic matter into the benthic food web (Maire et al, 2010), especially at higher temperatures (Zhang et al, 2013). To conclude, given that benthic foraging is a common feeding behaviour in freshwater environments observed all year round and that it appears a substantial zoogeomorphic mechanism (Pledger et al, 2014), SSD by fish should not be overlooked in future research assessing the potential impacts of climate change on zoogeomorphology.…”
Section: Discussionmentioning
confidence: 99%
“…In lentic waters, turbidity could be hastened and concentrations in nutrients and organic material higher due to the resuspension of sediments to the water column through bioturbation by fish (e.g., Breukelaar et al, 1994;Matsuzaki et al, 2009), resulting subsequently in phytoplankton blooming and water eutrophication, already enhanced by warming (Jeppesen et al, 2010). Changes in community composition (Matsuzaki et al, 2009) and vertical distribution of benthic fauna (Persson and Svensson, 2006b) due to predation by benthivorous fish may also impact nutrients fluxes as well as the incorporation of organic matter into the benthic food web (Maire et al, 2010), especially at higher temperatures (Zhang et al, 2013). To conclude, given that benthic foraging is a common feeding behaviour in freshwater environments observed all year round and that it appears a substantial zoogeomorphic mechanism (Pledger et al, 2014), SSD by fish should not be overlooked in future research assessing the potential impacts of climate change on zoogeomorphology.…”
Section: Discussionmentioning
confidence: 99%
“…And the "Ventilating" behavior improves water exchange and accelerates the flux of certain solutes, such as oxygen, carbon, nitrogen, and other nutrients, at the sedimentwater interface (Forster and Graf, 1995;Van Hoey, 2006;Duport et al, 2007;Na et al, 2008;Turek and Hoellein, 2015;Pascal et al, 2019). Substance flux tend to increase with temperature and the density of benthic animals at the sediment-water interface (Mahl et al, 2009;Zhang et al, 2013). However, bioirrigation-driven substance flux may reach a stable level at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Bioturbation encompasses two distinct processes, namely sediment reworking (i.e., the movements of sediment particles and associated organic matter) and burrow ventilation, which causes bioirrigation (i.e., the exchange of water and solute between the overlying water column and porewater) (Pascal et al, 2019). The ecological functions of bioturbation have been well studied (Zhang et al, 2013;Yazdani Foshtomi et al, 2018;Mustajärvi et al, 2019), some of which showed that the bioturbation could accelerate the biogeochemistry process of the sediment. Infauna perform bioturbation through daily activities, such as feeding, excretion, burrowing, and movement; these activities strongly affect sediment biogeochemistry (Duport et al, 2006;Mustajärvi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, which may increase bacterial metabolism, and bioturbation are parameters that initially affect the oxygen availability in sediments, thus indirectly conditioning diagenetic processes (Kristensen et al, 1992;Sundby, 2006;Ferreira, 2010;Zhang et al, 2013). In the Patos Lagoon estuary, Southern Brazil, oxygen availability in sediments is strongly associated with local hydrodynamics.…”
mentioning
confidence: 99%